Indigenous and Local Community Participation in the Multi-Level Governance of the Oxapampa-Ashaninka-Yanesha Biosphere Reserve in Peru - Lombira Alcantara,Florangel Lubitsa (2025)
This thesis examines the extent to which Indigenous and local communities are able to meaningfully participate in the governance of the Oxapampa-Ashaninka-Yanesha Biosphere Reserve (BIOAY). Peru is a mega-diverse country and has eight Biosphere Reserves, which operate through a multilevel governance model that prioritizes Indigenous and local participation for successful sustainable development outcomes. Nevertheless, growing socio-ecological challenges have raised concerns about the effectiveness of such participation, particularly in BIOAY. Using a qualitative case study design, data were collected through semi-structured interviews, a focus group, and document analysis to capture key insights into stakeholder perspectives and governance processes. The analysis draws on Cohen and Uphoff’s (1980) framework on participation in rural development, Aguilar-Støen’s (2015) work on power and participation, and Piattoni’s (2010) multi-level governance analytical framework. Findings reveal an important divide: while Indigenous and local communities frame participation as a bottom-up, rights-based process essential to territorial governance, state actors, international organizations, NGOs, and civil society conceptualize it as a top-down process to enhance governance effectiveness, sidelining its political dimension. Power asymmetries, a byproduct from the colonial legacy in Peru, are argued to be at the center of this divergence, which systematically limits Indigenous and local participation to a symbolic act.
Keywords: Participatory approach; multi-level governance; Indigenous communities; local communities; power asymmetries